Steel for high-strength bridge cable and preparation method thereof

By normalizing, quenching, tempering and rotary forging deformation of AISI 4340 medium-carbon low-alloy steel, high-strength bridge cable steel was obtained, and the problems of insufficient tensile strength and high production cost of existing bridge cable wires were solved, and the problem of insufficient tensile strength and high production cost of existing bridge cable wires was achieved. Efficient and low-cost production results.

CN119464658APending Publication Date: 2025-02-18NANJING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410663534.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The tensile strength of existing bridge cable wires cannot meet the needs of future high-span bridge construction, and the production costs are relatively high.

Method used

Using AISI 4340 medium-carbon low alloy steel as raw material, high-strength bridge cables with ultrafine crystal ferrite and nano-scale cementite particles were obtained through normalization, quenching, tempering and multi-pass room temperature rotary forging deformation. steel.

Benefits of technology

The tensile strength of the steel wire reaches more than 2000MPa, reduces production costs, simplifies processes, improves processing accuracy, and meets the needs of high-span bridges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464658A_ABST
    Figure CN119464658A_ABST
Patent Text Reader

Abstract

The invention relates to steel for a high-strength bridge cable and a preparation method of the steel. Comprising the following steps that (1) normalizing treatment is conducted, specifically, an AISI 4340 medium-carbon low-alloy steel bar is subjected to heat preservation for 0.5-2.5 h at the temperature of 770-920 DEG C, and air cooling is conducted to the room temperature; (2) quenching treatment is conducted, specifically, the bar obtained in the step (1) is subjected to heat preservation for 0.5-2.5 h at the temperature of 740-950 DEG C, and water cooling is conducted to the room temperature; (3) tempering treatment is conducted, specifically, the bar obtained in the step (2) is subjected to heat preservation for 0.5-3.5 h at the temperature of 530-650 DEG C, water cooling is conducted to the room temperature, and a bar with a ferrite and granular cementite initial structure is obtained; and (4) rotary swaging deformation is conducted, specifically, the bar obtained in the step (3) is subjected to multi-pass room-temperature rotary swaging, the dependent variable is controlled to be 2.0-4.0, and the high-strength bridge cable steel with ultra-fine grain ferrite and nanoscale cementite particles is obtained. The high-strength steel for the bridge cable is obtained through the simple machining technology combining pretreatment with rotary swaging, meanwhile, the cost is effectively reduced, extremely high economic benefits are brought, and wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal material preparation, and particularly relates to high-strength steel for bridge cables and a preparation method thereof. Background Art

[0002] The development trend of modern bridges is to continuously increase the span of bridges. Suspension bridges and cable-stayed bridges have great advantages in this regard. Their excellent spanning capacity makes them occupy an important position in bridge design. High-span cable-stayed bridges also put forward extremely high standards and requirements for the strength of steel wires. The latest cable-stayed cable manufacturing technology can make the strength of steel wires reach 2000MPa. In the development trend, bridge construction is facing problems such as increasing spans and increasingly complex construction environments. The existing strength of bridge cable steel wires cannot meet future development needs. At the same time, the continuous development of high-strength bridge cables can reduce consumables, reduce deadweight, and save costs. For every 100MPa increase in the tensile strength of steel wires, the total weight of the main cable can be reduced by 3%-5%, saving 1% of the total investment in the bridge. Therefore, the development of ultra-high-strength bridge cable steel above 2000MPa has broad development prospects.

[0003] Pearlite steel is usually processed into steel wire by cold drawing process to be used in the field of bridge cables. Chinese patent CN109468530A discloses a method for hot-rolled wire rods for galvanized steel wire for bridge cables above 2000MPa. The carbon content of the raw materials in this patent is between 0.90% and 1.10%. Although the tensile strength of the steel wire is ≥2000MPa, the high carbon content means high cost, which is not conducive to long-term production development. Replacing expensive high-carbon steel wire with low-cost medium-carbon low-alloy steel can significantly reduce production costs. In recent years, some scholars have studied the use of medium-carbon low-alloy steel to replace high-carbon steel, and used traditional drawing processes to prepare high-strength steel for bridge cables. After severe plastic deformation, the strength of medium-carbon steel wire is comparable to that of high-carbon steel wire, and the production cost can be reduced by 30-60%. Chinese patent CN112501506A discloses a steel wire rod for bridge cables and a method for manufacturing the same. The patent uses a traditional drawing process to obtain a pearlite steel wire with a strength of 1860 MPa, but cold drawing has disadvantages such as many steps, complicated operations, and insufficient processing precision. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method of high-strength steel for bridge cables. By reducing the carbon content, AISI 4340 medium-carbon low-alloy steel is used as raw material, and it is pretreated to obtain an easily deformable granular pearlite structure. After multiple rotary forging deformation, a high-strength steel for bridge cables with a structure of ultrafine ferrite and nano-scale cementite particles is obtained.

[0005] The technical solution to achieve the purpose of the present invention is: a method for preparing high-strength steel for bridge cables, comprising the following steps:

[0006] Step (1): Normalizing treatment: heat the AISI 4340 medium carbon low alloy steel bar at 770-920°C for 0.5-2.5h and air cool to room temperature;

[0007] Step (2): quenching treatment: the rod obtained in step (1) is kept at 740-950° C. for 0.5-2.5 h, and then water-cooled to room temperature;

[0008] Step (3): Tempering treatment: the rod obtained in step (2) is kept at 530-650° C. for 0.5-3.5 h, and water-cooled to room temperature to obtain a rod having an initial structure of ferrite + granular cementite;

[0009] Step (4): Rotary forging deformation: The rod obtained in step (3) is subjected to multiple passes of room temperature rotary forging, and the strain is controlled at 2.0 to 4.0 to obtain high-strength bridge cable steel with ultrafine ferrite and nano-scale cementite particles.

[0010] Further, the composition of AISI 4340 medium carbon low alloy steel is as follows by weight percentage: C: 0.34-0.41%, Si: 0.21-0.28%, Mn: 0.52-0.63%, Ni: 1.38-1.44%, Mo: <0.2%, S: <0.004%, P: <0.0047%, and the balance is Fe and other inevitable impurities.

[0011] Furthermore, in step (1), the initial diameter of the AISI 4340 medium carbon low alloy steel bar is 20 to 40 mm.

[0012] Furthermore, the normalizing treatment in step (1), the quenching treatment in step (2) and the tempering treatment in step (3) are all carried out in a box-type resistance furnace in an air atmosphere.

[0013] Furthermore, in step (4), the diameter reduction of the rod in each pass of room temperature rotary forging is 0.2-0.5 mm, and the final diameter of the rod is 5.5-26 mm.

[0014] Furthermore, high nitrogen austenitic stainless steel or 316L stainless steel is used instead of AISI 4340 medium carbon low alloy steel.

[0015] A high-strength steel for bridge cables is prepared by the above method.

[0016] According to the above-mentioned high-strength steel for bridge cables, the grain size of ferrite is 110-1220 nm, and the equivalent diameter of cementite is 45-70 nm.

[0017] Compared with the prior art, the present invention has the following significant advantages:

[0018] (1) The present invention replaces expensive high-carbon steel wire with low-cost medium-carbon low-alloy steel by reducing the carbon content, and uses rotary forging technology to replace traditional cold drawing, thereby simplifying the production process, improving processing accuracy, and reducing production costs; at the same time, the granular pearlite structure obtained after pretreatment has much better plasticity and toughness than the lamellar pearlite structure, and the cold deformation performance and processability are also better. At the same time, cementite as the second phase particle can improve the strength of the steel wire to a certain extent. The strength of the AISI 4340 alloy steel after rotary forging deformation is comparable to that of high-carbon steel.

[0019] (2) The process provided by the present invention is not limited to the AISI 4340 alloy steel, and can also be used for other metal materials, such as high nitrogen austenitic stainless steel, 316L stainless steel, etc., by appropriately changing the parameters. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the SEM image of the pretreated tissue in Example 1.

[0021] Figure 2 This is the TEM image of the room temperature rotary forging structure of the finished steel in Example 1.

[0022] Figure 3 This is the engineering stress-strain curve of the finished steel in Example 1. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0024] A method for preparing high-strength steel for bridge cables comprises the following steps:

[0025] Step (1): Normalizing treatment: heat the AISI 4340 medium carbon low alloy steel bar at 770-920°C for 0.5-2.5h and air cool to room temperature;

[0026] Step (2): quenching treatment: the rod obtained in step (1) is kept at 740-950° C. for 0.5-2.5 h, and then water-cooled to room temperature;

[0027] Step (3): Tempering treatment: the rod obtained in step (2) is kept at 530-650° C. for 0.5-3.5 h, and water-cooled to room temperature to obtain an initial structure of ferrite + granular cementite;

[0028] Step (4): Rotary forging deformation: The initial rod obtained by pretreatment in step (3) is subjected to multiple passes of room temperature rotary forging, and the strain is controlled at 2.0 to 4.0. As the strain increases, the ferrite grains are significantly refined under the action of stress and gradually transform into lamellar grains. Large-sized cementite particles will be broken under the action of deformation force, and eventually smaller-sized granular cementite particles will be formed. The dislocation density inside the ferrite grains is significantly increased. Under the synergistic effect of grain refinement, second phase strengthening and dislocation strengthening, a high-strength bridge cable steel with an organization of ultrafine-grained ferrite and nano-scale cementite particles is finally obtained.

[0029] The chemical composition of AISI 4340 medium carbon low alloy steel is as follows by weight: C: 0.34-0.41%, Si: 0.21-0.28%, Mn: 0.52-0.63%, Ni: 1.38-1.44%, Mo: <0.2%, S: <0.004%, P: <0.0047%, the remainder is Fe and other inevitable impurities, and the total weight percentage of each component is 100%.

[0030] The normalizing treatment in step (1), the quenching treatment in step (2) and the annealing treatment in step (3) are all carried out in a box-type resistance furnace in an air atmosphere.

[0031] The cooling rate of water cooling in step (2) and step (3) is 10 to 50°C / s.

[0032] The initial diameter of the AISI 4340 alloy steel bar in step (1) is 20 to 40 mm.

[0033] In step (4), the diameter reduction of the rod in each pass of room temperature rotary forging is 0.2-0.5 mm, and the final diameter of the rod is 5.5-26 mm.

[0034] The microstructure of AISI 4340 alloy steel consists of ultrafine-grained ferrite and nanometer-scale cementite particles. The grain size of ferrite is about 110-1220nm, and the equivalent diameter of cementite is about 45-70nm.

[0035] Example 1

[0036] The initial diameter of the AISI 4340 alloy steel bar in this embodiment is 30 mm, and its chemical composition by weight percentage is: C: 0.35%, Si: 0.24%, Mn: 0.55%, Ni: 1.39%, Mo: 0.2%, S: 0.004%, P: 0.0047%, and the balance is Fe and other inevitable impurities. The total weight percentage of each component is 100%.

[0037] A method for preparing high-strength steel for bridge cables of the present invention specifically comprises the following steps:

[0038] Step (1): Normalizing treatment: AISI 4340 medium carbon low alloy steel bar is kept at 850°C for 2 h and air-cooled to room temperature;

[0039] Step (2): quenching treatment: the rod obtained in step (1) is kept at 850°C for 2 hours and then cooled to room temperature with water;

[0040] Step (3): Tempering treatment: The rod obtained in step (2) is kept at 600° C. for 2 h, and water-cooled to room temperature to obtain an initial structure of ferrite + granular cementite;

[0041] Step (4): Rotary forging deformation: The initial rod obtained by pretreatment in step (3) is subjected to multiple passes of room temperature rotary forging, with the diameter reduction of each pass being 0.2 mm, the final strain being 3.0, and the final diameter of the rod being 6.6 mm.

[0042] The microstructure of AISI 4340 alloy steel after pretreatment in step (3) is as follows: Figure 1 As shown, the initial structure is composed of ferrite and cementite, the grain size of ferrite is 1220nm, and the equivalent diameter of cementite is 68.5nm.

[0043] The microstructure of the finished high-strength bridge cable steel in step (4) is as follows: Figure 2 As shown, the grain size of ferrite is 132nm and the equivalent diameter of cementite is 46.1nm. The ferrite grain size after rotary forging is reduced from 1220nm in the initial state to 132nm. Compared with the cold drawing deformation, the ferrite grains are obviously finer; the equivalent diameter of cementite particles is reduced from 68.5nm in the initial state to 46.1nm, and is dispersed in the ferrite matrix. Compared with the cementite lamellae, the formation of nano-scale granular cementite can effectively pin dislocations.

[0044] The mechanical properties of the finished steel are tested, and the corresponding engineering stress-strain curve is as follows: Figure 3 As shown in the figure, its yield strength and tensile strength are 2175MPa and 2196MPa respectively, and the total elongation is 1.9%. Under the induction of deformation force, the ferrite grains are significantly refined, the dislocation density increases, and the cementite particles undergo severe plastic deformation. The synergistic effect of grain refinement, dislocation strengthening and second phase strengthening greatly improves the strength of the finished steel, making the strength of AISI4340 alloy steel after rotary forging deformation not lower than that of high carbon steel.

[0045] Example 2

[0046] The initial diameter of the AISI 4340 alloy steel bar in this embodiment is 32 mm, and its chemical composition by weight percentage is: C: 0.36%, Si: 0.26%, Mn: 0.54%, Ni: 1.39%, Mo: 0.18%, S: 0.0037%, P: 0.0045%, and the balance is Fe and other inevitable impurities. The total weight percentage of each component is 100%.

[0047] A method for preparing high-strength steel for bridge cables of the present invention specifically comprises the following steps:

[0048] Step (1): Normalizing treatment: The AISI 4340 medium carbon low alloy steel bar is kept at 800°C for 2.5 h and air-cooled to room temperature;

[0049] Step (2): quenching treatment: the rod obtained in step (1) is kept at 850°C for 1.5 hours and then cooled to room temperature with water;

[0050] Step (3): Tempering treatment: The rod obtained in step (2) is kept at 650° C. for 2 h, and water-cooled to room temperature to obtain an initial structure of ferrite + granular cementite;

[0051] Step (4): Rotary forging deformation: The initial rod obtained by pretreatment in step (3) is subjected to multiple passes of room temperature rotary forging, with the diameter reduction of each pass being 0.2 mm, the final strain being 3.1, and the final diameter of the rod being 6.3 mm.

[0052] Example 3

[0053] The initial diameter of the AISI 4340 alloy steel bar in this embodiment is 28 mm, and its chemical composition by weight percentage is: C: 0.38%, Si: 0.25%, Mn: 0.59%, Ni: 1.42%, Mo: 0.18%, S: 0.0039%, P: 0.0044%, and the balance is Fe and other inevitable impurities. The total weight percentage of each component is 100%.

[0054] A method for preparing high-strength steel for bridge cables of the present invention specifically comprises the following steps:

[0055] Step (1): Normalizing treatment: AISI 4340 medium carbon low alloy steel bar is kept at 850°C for 2 h and air-cooled to room temperature;

[0056] Step (2): quenching treatment: the rod obtained in step (1) is kept at 900°C for 1.5 hours and then cooled to room temperature with water;

[0057] Step (3): Tempering treatment: The rod obtained in step (2) is kept at 600° C. for 2.5 hours, and water-cooled to room temperature to obtain an initial structure of ferrite + granular cementite;

[0058] Step (4): Rotary forging deformation: The initial rod obtained by pretreatment in step (3) is subjected to multiple passes of room temperature rotary forging, with the diameter reduction of each pass being 0.4 mm, the final strain being 2.8, and the final diameter of the rod being 7.5 mm.

Claims

1. A method for preparing high-strength steel for bridge cables, characterized in that: The steps include: Step (1): Normalizing treatment: heat the AISI 4340 medium carbon low alloy steel bar at 770-920°C for 0.5-2.5h and air cool to room temperature; Step (2): quenching treatment: the rod obtained in step (1) is kept at 740-950° C. for 0.5-2.5 h, and then water-cooled to room temperature; Step (3): Tempering treatment: the rod obtained in step (2) is kept at 530-650° C. for 0.5-3.5 h, and water-cooled to room temperature to obtain a rod having an initial structure of ferrite + granular cementite; Step (4): Rotary forging deformation: The rod obtained in step (3) is subjected to multiple passes of room temperature rotary forging, and the strain is controlled at 2.0 to 4.0 to obtain high-strength bridge cable steel with ultrafine ferrite and nano-scale cementite particles.

2. The method according to claim 1, characterized in that The composition of AISI 4340 medium carbon low alloy steel is as follows by weight percentage: C: 0.34-0.41%, Si: 0.21-0.28%, Mn: 0.52-0.63%, Ni: 1.38-1.44%, Mo: <0.2%, S: <0.004%, P: <0.0047%, and the balance is Fe and other inevitable impurities.

3. The method according to claim 2, characterized in that In step (1), the initial diameter of the AISI 4340 medium carbon low alloy steel bar is 20 to 40 mm.

4. The method according to claim 3, characterized in that The normalizing treatment in step (1), the quenching treatment in step (2) and the tempering treatment in step (3) are all carried out in a box-type resistance furnace in an air atmosphere.

5. The method according to claim 4, characterized in that In step (4), the diameter reduction of the rod in each pass of room temperature rotary forging is 0.2-0.5 mm, and the final diameter of the rod is 5.5-26 mm.

6. The method according to claim 1, characterized in that High nitrogen austenitic stainless steel or 316L stainless steel is used instead of AISI 4340 medium carbon low alloy steel.

7. A high-strength steel for bridge cables, characterized in that: The method is prepared by any one of claims 1 to 5.

8. The high-strength steel for bridge cables according to claim 7, characterized in that: The grain size of ferrite is 110-1220 nm, and the equivalent diameter of cementite is 45-70 nm.

Citation Information

Patent Citations

  • Hot-rolled steel wire rod for large bridge cable rope zinc-plated steel wire over 2000 MPa level and production method

    CN109468530A

  • Steel wire rod for bridge cable and manufacturing method thereof

    CN112501506A